Phosphorus input through fog deposition in a dry tropical forest. Issue 12 (2nd December 2015) - Vandecar, Karen L.; Runyan, Christiane W.; D'Odorico, Paolo; Lawrence, Deborah; Schmook, Birgit; Das, Rishiraj
Abstract: In many tropical forests, where phosphorus (P) is considered a limiting nutrient, atmospheric deposition can contribute significantly to available P. Previous studies have shown that P inputs from atmospheric deposition are enhanced by plant canopies. This effect is explained as the result of increased deposition of P‐rich aerosol particles (dry deposition) and fog droplets (fog or "occult" deposition) onto leaf surfaces. Here we studied the importance of fog as a source of P to a P‐limited dry tropical forest. Throughout an 80 day period during the dry season when fog is most common, we sampled fog water and bulk precipitation in a clearing and measured leaf wetness and throughfall in an adjacent secondary and mature forest stand. During the study period, total P ( PT ) concentrations in fog water ranged from 0.15 to 6.40 mg/L, on average fourteenfold greater than PT concentrations in bulk precipitation (0.011 to 0.451 mg/L), and sixfold and sevenfold greater than throughfall PT concentrations in the secondary and mature forest stands, respectively (0.007 to 1.319 mg/L; 0.009 to 0.443 mg/L). Based on leaf area index, the frequency of fog deposition, and amount of water deposited per fog event, we estimate that fog delivers a maximum of 1.01 kg/ha/yr to secondary forest stands and 1.75 kg/ha/yr to mature forest stands, compared to 0.88 kg/ha/yr to secondary forest stands and 1.98 kg/ha/yr to mature forest stands via throughfall (wet + dry deposition) and stemflow. Thus, fog deposition may contribute substantially to available P in tropical dry forests. Key Points: Fog P deposition varies depending on forest canopy characteristics Fog water delivered a substantial amount of P (phosphorus) Deforestation may reduce this input and increase P limitation